Causality of Islamic Banking Financial Performance in Indonesia - Nur Hafizhah Putri; Asbi Amin; Anwar (IECON, 2024)
This study aims to test whether capital structure, liquidity, financing to deposit ratio (FDR), and operations efficiency ratio (OER) affect financial performance in Islamic banking companies registered with the Financial Services Authority (OJK) in 2019-2023. Data collection uses secondary data obtained from financial reports, using purposive sampling techniques. The population in this study is Islamic banking companies registered with the Financial Services Authority (OJK) in 2019-2023, with a total of 14 observations, while the sample taken is 40 observations. The analysis method uses multiple linear regression techniques and hypothesis testing. The results of the study indicate that capital structure has a significant positive effect on financial performance, liquidity has a significant positive effect on financial performance, financing to deposit ratio (FDR) does not affect financial performance, and operations efficiency ratio (OER) does not affect financial performance.